HORTATORY AND ANALYTICAL EXPOSITION ANALYSIS ON STUDENT’S WRITING - Ratu Dea Mada; Eva Fachriyah; Arifiatul Hasanah (FKIP, Universitas Banten Jaya, 2022)
This research aims to identify how students at second semester in University of Serang Raya can differentiate between hortatory and Analytical Expositions. The method used is descriptive study. The sample of this research are 7 classes of second semester in University of Serang Raya. The tool for data collecting was a written text that students wrote in two kinds of text, Hortatory and Analytical Exposition in a side by side form (2 columns) and a quiz in a google forms. It is hope that by analysing the students’ writing, they are able to comprehend and differentiate the structure and the content of Hortatory and Analytical Exposition